2011
DOI: 10.1111/j.1524-4725.2011.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Q-Switched Alexandrite Laser in Treating Nevus of Ota

Abstract: The QSAL is a safe and effective modality for treating nevus of Ota. Recurrence was rare and appeared beyond the previously treated sites. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…We read with interest the study of Kar et al, [1] but we would like to put in to perspective the optimistic outcome reported in view of the published data [2][3][4][5][6][7][8][9][10][11] [Table 1, Figure 1] and our findings [ Figure 2]. Our results with Q-switched Nd:YAG are not as heartening, as the majority of the patients have <25% response [ Figure 2].…”
Section: Sirmentioning
confidence: 60%
See 3 more Smart Citations
“…We read with interest the study of Kar et al, [1] but we would like to put in to perspective the optimistic outcome reported in view of the published data [2][3][4][5][6][7][8][9][10][11] [Table 1, Figure 1] and our findings [ Figure 2]. Our results with Q-switched Nd:YAG are not as heartening, as the majority of the patients have <25% response [ Figure 2].…”
Section: Sirmentioning
confidence: 60%
“…It would have been better if the cases of bilateral nevus were excluded from the analysis, as they have a universally poor result. [2,3,[5][6][7][8][9][10][11] Moreover, in the methods, the goal was to continue sittings till complete improvement or 15 sittings, but 36 out of 50 patients did not achieve this goal. If we accept the conclusion that >10 sittings are better and also that no added benefit was achieved beyond 12 sittings, it is difficult to comprehend that a marked difference in response was seen within two sittings (12 versus 10).…”
Section: Sirmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevus of Ota caused by dermal melanocytosis affects approximately 0.02% of the Asian population . The clinical manifestation of nevus of Ota is a unilateral brown to slate blue mottled hyperpigmentation along the distributions of the ophthalmic or maxillary divisions of the trigeminal nerve . Q‐switched laser systems using ruby, alexandrite, or Nd:YAG lasers were used to treat this condition.…”
Section: Introductionmentioning
confidence: 99%